A bibliometric analysis of transcranial alternating current stimulation - Wu, Cheng-Fan; Shen, Chao; Wang, Zhao-Di; Gong, Yan; Zhou, Lu-Han; Qian, Wen-Jun; Tang, Tong (Frontiers in Neuroscience, 2024)
Background: Transcranial alternating current stimulation (tACS) can apply currents of varying intensity to the scalp, modulating cortical excitability and brain activity. tACS is a relatively new neuromodulation intervention that is now widely used in clinical practice. Many papers related to tACS have been published in various journals. However, there are no articles that objectively and directly introduce the development trend and research hotspots of tACS. Therefore, the aim of this study is to use Citespace to visually analyze the recent tACS-related publications, systematically and in detail summarize the current research hotspots and trends in this field, and provide valuable information for future tACS-related research. Material and Methods: The database Web of Science Core Collection Science Citation Index Expanded was used and searched from build to August 4, 2023. Using the CiteSpace to analyze the authors, institutions, countries, keywords, co-cited authors, journals, and references. Results: A total of 677 papers were obtained. From 2008 to 2023, the number of publications shows an increasing trend, albeit with some fluctuations. The most productive country in this field was Germany. The institution with the highest number of publications is Carl von Ossietzky University of Oldenburg (n = 50). According to Bradford's law, 7 journals are considered core journals in the field. Herrmann, CS was the author with the most publications (n = 40), while Antal, A was the author with the highest number of co-citations (n = 391) and betweenness centrality (n = 0.16). Disease, neural mechanisms of the brain and electric stimulation are the major research areas in the field. The effect of tACS in different diseases, multi-site stimulation, combined treatment and evaluation are the future research hotspots and trends. Conclusion: tACS has research value and research potential, and more and more researchers are paying attention to it. The findings of this bibliometric study provide the current status and trends in the clinical research of tACS and may help researchers to identify hotspots s and explore new research directions in this field.